2014
DOI: 10.1051/0004-6361/201423758
|View full text |Cite
|
Sign up to set email alerts
|

First experimental constraints on the disformally coupled Galileon model

Abstract: Aims. The Galileon model is a modified gravity model that can explain the late-time accelerated expansion of the Universe. In a previous work, we derived experimental constraints on the Galileon model with no explicit coupling to matter and showed that this model agrees with the most recent cosmological data. In the context of braneworld constructions or massive gravity, the Galileon model exhibits a disformal coupling to matter, which we study in this paper. Methods. After comparing our constraints on the unc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 67 publications
(78 reference statements)
1
42
0
Order By: Relevance
“…Cosmological parameter analyses to test MG theories have been performed by several authors [340,884,895,896,903,[908][909][910][911][912][913]. Specific studies to determine the cosmological impact of galileon theories and to constrain model parameters appear in [265,[914][915][916][917][918][919][920].…”
Section: Cosmological Testsmentioning
confidence: 99%
“…Cosmological parameter analyses to test MG theories have been performed by several authors [340,884,895,896,903,[908][909][910][911][912][913]. Specific studies to determine the cosmological impact of galileon theories and to constrain model parameters appear in [265,[914][915][916][917][918][919][920].…”
Section: Cosmological Testsmentioning
confidence: 99%
“…We found that the amplitude of the low-l region of the CMB power spectrum, which is mostly determined by the Integrated Sachs-Wolfe (ISW) effect, plays a decisive role in constraining the parameter space of the Galileon model. The use of the full shape of the CMB temperature data results in much tighter constraints than those obtained by using only the information encoded in the CMB distance priors [16]. Reference [28] finds that the bestfitting Galileon models to the WMAP9 data [51] have a lower ISW power relative to ΛCDM, which results in a better fit.…”
Section: Overview Of Previous Observational Constraintsmentioning
confidence: 99%
“…References [20,21] explored the phenomenology of the Galileon model at the background level, and derived observational constraints using data from type 1 See, e.g., Refs. [13][14][15][16][17][18][19] for studies of models motivated in similar ways.…”
Section: Introductionmentioning
confidence: 99%
“…The way the background cosmological evolution can be affected in Galileon models has already been studied and constrained using observational probes of the geometry of the Universe, such as type Ia supernovae (SNIa), the scale of the baryonic acoustic oscillations (BAO) feature in the galaxy distribution and the position of the peaks of the cosmic microwave background (CMB) angular power spectrum of temperature fluctuations [65][66][67][68][69][70][71]. Furthermore, by studying the evolution of density fluctuations in linear perturbation theory, it has also been shown how Galileon models can be constrained theoretically, by the imposition of conditions to avoid the presence of ghosts and other pathologies [67,69], and observationally, by investigating the predictions for the growth rate of large scale structure [70][71][72][73] and for the full CMB, linear matter and weak lensing potential power spectra [74] (see also [75] for a study of the bispectrum of the matter fluctuations).…”
Section: Introductionmentioning
confidence: 99%